Niveles de comprensión lectora en alumnos de cuarto grado de primaria de Carmen de La Legua Reynoso - Callao - Escate Portal, Gilda Maribel (2012)
This descriptive investigation aims to describe the reading comprehension levels of the fourth grade primary students from public schools in Carmen de la Legua Reynoso distric, Callao. We applied the ACL to the sample made of 457 students to 4to. Primary grade, the results show that most of these students reach a low level in reading comprehension. They reach an average level in literal dimension; however, they reach very low in reorganizational dimension and low in inferential and critical dimension, most of the male students present a higher level than female. We conclude that the students should improve the more complex dimensions of reading comprehension to strengthen their learning.